UPAYA MENINGKATKAN KEMAMPUAN BACA TULIS ALQUR’AN (BTQ) PESERTA DIDIK MELALUI METODE RUBAIYAT DI SEKOLAH DASAR INPRES (SD) 6 LOLU PALU - Khairiyah Khairiyah; Arfan Arfan; Kasmiati Kasmiati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This research discusses the efforts of teachers in improving the literacy ability of the Qur’an students through the rubaiyat method at SD Inpres 6 Lolu Palu. The formulation of the problem in this research is how is the teacher's effort to improve the students' literacy in reading and writing through the rubaiyat method in SD Inpres 6 Lolu Palu? and what are the supporting factors and inhibiting factors in improving students' literacy in the Qur’an through the rubaiyat method? This type of research used in this thesis is qualitative research. Data collection techniques used were observation (interviews) and documentation. Furthermore, the data analysis used is data reduction and data presentation. In an effort to improve the literacy skills of the Qur’an (BTQ) students through the rubaiyat method in SD Inpres 6 Lolu Palu, teachers as educators give efforts to give the task of writing verses that are in the Qur’an namely, memorizing short suras, and teaching recitation. Based on the results of research conducted by the author In an effort to improve the literacy skills of students through the rubaiyat method there are several factors, namely supporting factors and inhibiting factors. As for the supporting factors in improving the students' literacy in the Qur’an, students are facilities such as books, fans, the Qur’an and iqra, as well as a comfortable classroom. While the inhibiting factor is the lack of media or teaching aids that are used during the learning process. The implication in this research is the government, all schools, especially school principals, PAI teachers, and BTQ teachers can work together in improving the students' literacy skills through the rubaiyat method in order to be able to emphasize students more about the importance of learning the Qur’an and reading it according to science Tajweed.